Kuantitas Dan Kualitas Sel Telur Anjing Lokal Dari Berbagai Stadium Estrus - Yuda Heru Fibrianto; Tri Wahyu Pangestiningsih; Amelia Hanna; Pudji Astuti; ClaudeM Mona Airin; Asyhari .; Amrullah Anindito; Nuraini Rahmawati; Koko Kurniawan; Pradityo Yoga Wibowo (Jurnal Sain Veteriner, 2008)
.